Correlation Analysis Of Clinical And Immunological Parameters In Patients With AD, COPD, AND ACO - FayzullaevaN.Ya (Universitas Muhammadiyah Sidoarjo, 2022)
Due to the significant prevalence of chronic nonspecific lung diseases and the high level of disability, one of the most important tasks of healthcare is the prevention and effective diagnosis, as well as the treatment of patients withchronic diseases of the lower respiratory tract. Asthma and chronic obstructive pulmonary disease (COPD) are a major public health problem and a leading cause of morbidity and mortality worldwide. Asthma and COPD are the most common chronic respiratory diseases, each with a specific pathophysiology. Usually, asthma is characterized by chronic inflammation of the airways with reversible symptoms, while COPD is characterized by persistent respiratory changes in the bronchopulmonary system. However, patients can sometimes have clinical features of both diseases, and this condition is called asthma-COPD overlap (ACO). recommended by the joint guidelines of GINA (Global Strategy for the Management and Prevention of Asthma) and GOLD (Global Initiative for Chronic Obstructive Pulmonary Disease). According to this guide, ACOis characterized by